Identifying the Influential Factors in the Change of Residential to Commercial Areas: a Case Study in Rungkut Madya, Surabaya - Bachtiar, Raditio; Soemardiono, Bambang; Septanti, Dewi (Institut Teknologi Sepuluh Nopember, 2020)
The development of road transport that increased on Jalan Rungkut madya in a few years has made A positive impact on an area in terms of the economy. However, the negative impact of that development is to make the changing function of land use to be a commercial area that disrupt the function. The changes in the area function unconsciously impact the changes in the city's design elements on which influences the quality of a design of the city. To find out what factors that affect the change of a function area is indispensable in becoming a reference in designing a good commercial area. The paradigm in this study uses the post-positivist paradigm, where this paradigm is a qualitative method that uses a scientific approach, the strategy used is combined strategy between quantitative and case studies. The primary Data used in this study came from observations and questionnaires. The results in this study included identifying influential factors in the change of residential functions into commercial areas.